Some effects of fine sediment on flow phenomena - Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; Haushild, W. L., author; U.S. Geological Survey, publisher (Colorado State University. Libraries, 1963)
Fine material (bentonite and kaolin clays) dispersed in water has a very definite effect on the viscosity and specific weight of the fluid. Tests at 24° C. with a Stormer viscosimeter showed that the apparent kinematic, viscosity of an aqueous dispersion consisting of 10 percent by weight bentonite was 8.75 times greater than that of pure water, and a dispersion consisting of kaolin was 1.40 times greater. The change is viscosity and density of the fluid changes the fall velocity of the bed material. The effect of fin material on the fall velocity of the bed material can be determined, as a first approximation, with the visual accumulation tube by using aqueous dispersions of clay as the sedimentation liquid. The results from visual accumulation analyses are comparable to those obtained by computation using the Reynolds number, drag relation, and the viscosity of the aqueous dispersion of clay as obtained from the Stormer viscosimeter. Experiments conducted in flumes at Colorado State University demonstrated that when changes in fall velocity caused by the changes in fluid properties occurred, the form of bed roughness was altered. Resistance to flow and sediment transport, because they are dependent on the form of bed roughness, were appreciably affected.
CER63-DBS-EVR-WLH56.
Keywords: Sedimentation and deposition